Gospoda-tovarishchi . Gospoda-tovarishchi . Gentlemen-Comrades . Господа-товарищи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing democratic factions in the State Duma. Featured in the program: Khakamada, Irina Mutsuovna (Politician) Contributors: Omel'ianiuk, Ol'ga (Anchor) Передача рассказывает о демократических фракциях в Государственной Думе. В программе участвуют: Хакамада, Ирина Муцуовна (Политик) Создатели: Омельянюк, Ольга (Ведущий/Ведущая)